EXPENDITURES OF THE STATE BUDGET: https://doi.org/10.5281/zenodo.14807621 - Ayitboyev, Nodirbek (Science technology&Digital finance, 2025)
This article is devoted to the topic of expenditures of the state budget and analyzes the composition of the state budget, types of expenditures and their impact on the economy. The article states that government spending is allocated to key areas such as social sectors, infrastructure, security, investment and social assistance. The methodologies, planning and forecasting processes, resource allocation and monitoring methods necessary for effective management of public spending are also covered in detail. The article also analyzes the economic impact of government budget expenditures, the role in promoting social welfare and supporting economic growth. In general, the article shows the importance of the state budget in the effective management of expenses and its results in ensuring economic stability.